Combined alkali and hydrothermal pretreatments for oat straw valorization within a biorefinery concept - Romaní, Aloia (2016)
The aim of this work was the evaluation of lime pretreatment combined or not with previous step of autohydrolysis for oat straw valorization. Under selected conditions of lime pretreatment, 96% of glucan and 77% of xylan were recovered and 42% of delignification was achieved. Xylose fermentation to ethanol by metabolic engineered Saccharomyces cerevisiae (MEC1133) strain improved the ethanol production by 22% achieving 41 g/L. Alternatively, first step of autohydrolysis (S0=4.22) allowed a high oligosaccharides recovery (68%) and subsequent lime pretreatment attained a 57% of delignification and 99% of glucan to glucose conversion. Oat straw processed by autohydrolysis and lime pretreatment reached the maximal ethanol concentration (50 g/L). Both strategies led to oat straw valorization into bioethanol, oligosaccharides and lignin indicating that these pretreatments are adequate as a first stage within an oat straw biorefinery.